Knee Surgery Reconstruction and Replacement - Bosco Sales Nogueira, João; Alberto Dias Leite, José; Heráclio Do Carmo Araújo, Leonardo; Cortez Bezerra, Marcelo (IntechOpen, 2020)
Knee Surgery - Reconstruction and Replacement is an intriguing book. From basic to advanced concepts, it collects relevant and reliable information obtained globally from validated collaborating researchers.